IMF Survey, Volume 33, Issue 22. (IMF Survey; IMF Survey ;, 2004)
Higher oil prices, a rising euro, and softer global demand are beginning to take their toll on Europe's brittle economic upturn. Will the euro area's two largest economies, Germany and France, be able to sustain their recoveries without losing sight of the pressing goals of fiscal consolidation and comprehensive structural reforms? Alessandro Leipold, mission chief for France and Deputy Director of the IMF's European Department, and Ajai Chopra, mission chief for Germany and Senior Advisor, talk with Conny Lotze of the IMF Survey about recent developments and how the two countries can meet the challenges ahead.